2020
DOI: 10.3390/ijms21020457
|View full text |Cite
|
Sign up to set email alerts
|

DM1 Phenotype Variability and Triplet Repeat Instability: Challenges in the Development of New Therapies

Abstract: Myotonic dystrophy type 1 (DM1) is a complex neuromuscular disease caused by an unstable cytosine thymine guanine (CTG) repeat expansion in the DMPK gene. This disease is characterized by high clinical and genetic variability, leading to some difficulties in the diagnosis and prognosis of DM1. Better understanding the origin of this variability is important for developing new challenging therapies and, in particular, for progressing on the path of personalized treatments. Here, we reviewed CTG triplet repeat i… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
33
0
2

Year Published

2020
2020
2023
2023

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 27 publications
(35 citation statements)
references
References 65 publications
0
33
0
2
Order By: Relevance
“…Based on this feature, separate congenital, infantile, juvenile, adult and late-onset forms of DM1 are described, with respective mean repeat lengths of ~1000, 800, 600, 400, and 200 according to clinical records ( Figure 4 ) [ 3 , 69 ]. Noteworthily, DM1 patients display high levels of CTG instability between different tissues of the same individual that correlate with variations in hypermethylation and clinical variability ( Figure 4 ) [ 3 , 69 , 70 ]. In DM1-affected human embryonic stem cell (hESC) lines, it has been observed that hypermethylation varies in relation to expansion size [ 71 ].…”
Section: Unstable Gc-rich Repeats In 3′ Untranslated Region (3′utrmentioning
confidence: 99%
“…Based on this feature, separate congenital, infantile, juvenile, adult and late-onset forms of DM1 are described, with respective mean repeat lengths of ~1000, 800, 600, 400, and 200 according to clinical records ( Figure 4 ) [ 3 , 69 ]. Noteworthily, DM1 patients display high levels of CTG instability between different tissues of the same individual that correlate with variations in hypermethylation and clinical variability ( Figure 4 ) [ 3 , 69 , 70 ]. In DM1-affected human embryonic stem cell (hESC) lines, it has been observed that hypermethylation varies in relation to expansion size [ 71 ].…”
Section: Unstable Gc-rich Repeats In 3′ Untranslated Region (3′utrmentioning
confidence: 99%
“…Individuals are classified into five categories based on the age at onset: congenital, infantile, juvenile, adult, and late-onset [39,40]. These are largely correlated with repeat size, but there is significant overlap between the categories [41]. Repeat lengths of 5-∼37 CTGs occur in the general population, and it is thought that alleles between 16 and 30 repeats are the source of rare de novo expansions [42].…”
Section: Introductionmentioning
confidence: 99%
“…Repeat lengths of 5-∼37 CTGs occur in the general population, and it is thought that alleles between 16 and 30 repeats are the source of rare de novo expansions [42]. Affected individuals can harbor from ∼50 to several thousand repeats, with congenital DM1 often presenting with alleles >1,000 CTGs [43,44], Repeats of ∼50-79 exhibit high levels of male germline expansion, whereas 80+ repeats tend to exhibit greater expansions in female transmissions [41]. Somatic instability can be detected in fetal tissues between 13 and 16 weeks of gestation, and in patients shows expansion-biased and tissue-dependent instability, with high levels seen in heart, skin, muscle and blood, as well as in brain tissues [41,45].…”
Section: Introductionmentioning
confidence: 99%
“…Among the trinucleotide repeat (TNR) diseases, Fragile X syndrome (FXS (MIM: 300624)), Huntington’s disease (HD (MIM: 143100)), several spinocerebellar ataxias (SCAs) and myotonic dystrophy type 1 (DM1 (MIM: 160900)) have been reported. DM1 is a highly multisystemic disorder caused by an unstable CTG repeat expansion within the 3′-untranslated region (UTR) of the myotonic dystrophy protein kinase ( DMPK ) gene that usually increases across generations and in tissues [ 2 , 3 ]. DM1 is mainly characterized by a broad clinical spectrum of symptoms such as myotonia, muscle weakness, cardiac conduction defect, respiratory insufficiency, dysphagia, gastrointestinal symptoms, somnolence or cataracts [ 4 ].…”
Section: Introductionmentioning
confidence: 99%
“…However, many DM1 patients develop unusual DM1 symptoms or remain asymptomatic despite the presence of a large CTG repeat expansion in their cells. This suggests that contributing factors such as somatic mosaicism, gene modifiers and environmental factors may affect the evolution of the clinical and mutation aspects [ 3 , 6 , 7 ]. The somatic mosaicism observed in blood is strongly biased towards expansions and contributes not only to the progressive nature of the different symptoms in several DM1 ethnic groups, but also to the variation in the age of onset [ 6 , 8 , 9 , 10 ].…”
Section: Introductionmentioning
confidence: 99%